Global Brand Management with Emphasis on the Effect of Country of Origin - Krajnović, Aleksandra; Jadreško, Ivan; Bosna, Jurica (Oeconomica Jadertina, 2017)
Geographical expansion is inevitable destiny of brands because it determines the growth of the brand and its ability to innovate and maintain competitive advantage in terms of economies of scale and productivity. Therefore, brand managers are trying to find out new ways and approaches in a manner to achive international expansion. The effect that has been studied for a long time in relation with brands is the effect of the country of origin. Purpose of this paper is to find out the impact of the country of origin on the contemporary brand management. Goal of the paper is to point out the end of country of origin trend in developed countries and development of this effect in developing countries. More and more companies are currently trying to cover up the country of origin of the product while brend with its image represents more important and familiar information. Generally, the effect of country of origin becomes less important while the country of the brand has a growing importance.